Phytochemical study of the alkaloid from the dried stems of Artocarpus heterophyllus Lamarck (Family Moraceae) - Montejo, Cecilia V.
Artocarpus heterophyllus Lamarck (Family Moraceae), more commonly known as langka (Tagalog), and jackfruit (English), has always been studied for its glycoside content which is classified as a flavone or flavonoid.